ANALISIS KEBIJAKAN TATA KELOLA KOMUNIKASI DALAM MENINGKATKAN KINERJA LEMBAGA PENDIDIKAN - Ahmad Aziz Faozi; Sri Sumarsih; Nur Ing Ati (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2022)
The success of educational institutions is influenced by the effectiveness of communication governance within the organization. Effective communication ensures the smooth transmission of information, coordination, and stakeholder engagement. This study aims to analyze the effectiveness of communication governance at SDIT Ash-Shibgoh in improving institutional performance. Using a qualitative approach with interviews conducted with teaching staff, the study explores communication patterns, media used, challenges faced, and their impact on organizational effectiveness. The results indicate that the school has implemented a systematic formal communication structure through hierarchical procedures and utilizes digital technology, such as the Epskul application and WhatsApp, to enhance transparency and efficiency. However, some challenges were identified, including low parental responsiveness to digital information and limited access to technology for some stakeholders. To overcome these obstacles, strategies such as increasing parental involvement, providing communication training for staff, and optimizing the use of technology are recommended. Therefore, effective communication governance plays a crucial role in improving coordination, transparency, and the quality of educational services at SDIT Ash-Shibgoh